Immune responses to adenovirus vectors in the nervous system. - Wood, M; Charlton, H; Wood, K; Kajiwara, K; Byrnes, A (1996)
Non-replicating adenovirus vectors are being developed as vehicles for gene transfer into cells of the nervous system. An important requirement for successful gene transfer is the absence of deleterious cytotoxic or inflammatory side effects of the delivery system. Despite offering relatively stable reporter gene expression, currently available adenovirus vectors also elicit immune responses in the brain, both at the site of vector delivery and at synaptically linked distant sites. However, although an anti-viral T-lymphocyte response eliminates the vector and damages local tissue in many peripheral organs, the immune response to adenovirus in the brain is less effective and enables the vector to persist. Nevertheless, in this persistent state the adenovirus vector remains a potential target for a destructive immune response that can also cause local demyelination. The development of strategies to minimize this damaging immune response, through either vector modification or immunomodulation, will be crucial for the future success of genetic therapies in the brain.